Chinese smokers' behavioral response toward cigarette price: individual and regional correlates. Issue 1 (December 2016) - Yang, Tingzhong; Peng, Sihui; Yu, Lingwei; Jiang, Shuhan; Stroub, William; Cottrell, Randall; Rockett, Ian
Abstract Background Many studies have explored smokers' behavioral response to cigarette prices at the individual level, but none have factored in regional variation and determinants. This study addresses these research gaps in the Chinese context. Methods A cross-sectional multistage sampling process was used to recruit participants in 21 cities in China. Individual-level information was collected using standardized questionnaires. City-level variables were retrieved from a nationall database. Multilevel logistic regression analysis was used to assess price sensitivity variation at both individual and city levels. Results Among 5660 current smokers, 5.9 % used non-self-paying cigarettes, 32.8 % purchased cigarettes in cartons, and 5.2 % decreased their smoking expenditure due to price. Multilevel analysis showed that individual demographic and smoking expenditure characteristics and regional smoking restrictions in work places, cigarette production, and media news coverage are associated with price sensitivity. Conclusions This study adds substantially to the understanding of Chinese smokers' behavioral responses to cigarette prices. Increasing smoker sensitivity to cigarette prices will require stronger tobacco control and public education campaigns.